Frequency of Placenta Previa in Patients with Repeated C-Section - Faiza Dawood, Sadia Hanif, Sidra Pervaiz, Komal Farooqi, Maria Rehman, Nighat Afridi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the prevalence of placenta previa and adverse outcomes in patients with repeated C-sections. Study Design: Descriptive/Observational study Place and Duration: Gynaecology and Obstetrics Department, Combined Military Hospital, Peshawar for the period from February 2021 to January 2022. Methods: There were 60 pregnant women had age 20-50 years were presented. Pregnant women with the history of c-section were included in this study. After getting informed written consent demographics of included patients i.e age, body mass index, gestational age, parity and gravidity were recorded. After delivery, association of placenta previa was recorded. Maternal and fetus outcomes were also assessed in this study. SPSS 21.0 was used to analyze all data. Results: Majority of the cases 28 (46.7%) were aged between 20-30 years, 20 (33.3%) had age 31-40 years and 12 (20%) patients were aged between 41-50 years. 34 (56.7%) cases had BMI >25kg/m2 and 26 (43.3%) patients had BMI <25kg/m2. Mean parity of the patients was 4.7±3.21 and mean gestational age was 36.13±14.61 weeks. Frequency of placenta previa was found in 15 (25%) cases in which majority 9 (60%) were males and 6 (40%) were females. Among 15 cases of placenta previa, low apgar score, low birth weight and ICU admission were the adverse outcomes among new borns. In mothers, frequent bleeding, pre-eclampsia and gestational diabetes were the adverse events. Conclusion: The results of this research led us to the conclusion that the prevalence of placenta previa rises with an increasing number of prior caesarean sections and the associated negative fetomaternal outcome. Keywords: C-section, Placenta Previa, Adverse Events, Parity